2022
DOI: 10.3390/su14031174
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Water-Retaining and Mechanical Behaviors of Unbound Granular Materials under Infiltration

Abstract: Unbound granular materials (UGM) in permeable pavement will experience large numbers of infiltration during their service-life. The frequently changed moisture not only affects the cooling effect of permeable pavement, but also influences the mechanical behaviors of UGM. However, evidence is lacking to state the influence of infiltration on the behaviors of UGM, which is commonly in fully permeable pavement. Considering the influence of infiltration, this study conducted experimental tests to investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The fatigue life analysis in this study uses strain life as a control. Mechanical changes in the material are indicated by a decrease in the modulus of the material under plastic strain [34]. Several parameters affect the fatigue life: the applied load, surface area, and fatigue [35].…”
Section: Discussionmentioning
confidence: 99%
“…The fatigue life analysis in this study uses strain life as a control. Mechanical changes in the material are indicated by a decrease in the modulus of the material under plastic strain [34]. Several parameters affect the fatigue life: the applied load, surface area, and fatigue [35].…”
Section: Discussionmentioning
confidence: 99%
“…Then, there are three working conditions for UGM in permeable pavement: repeated load only, repeated load after infiltration, and simultaneous action with load and infiltration, respectively. Taking the working conditions into account, Li et al conducted experimental tests to investigate the effect on the water-retention, particle migration and bearing capacity of UGM considering the influence of infiltration [26]. However, plastic strain was not fully analyzed and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the main influence factor of this study, the used gradation of UGM was the median with 96% compactness at optimum moisture content. The improved PUMA test method was used for the investigation, which we referenced from a previous study in the literature [26]. In this study, the plastic strain and plastic strain rate were the main analysis indicators, the relationship between plastic strain and plastic strain rate, and the elastoplastic total strains, were also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Stolle et al observed that the nature of fine content also influences the moisture sensitivity of the resilient modulus of aggregate [18]. Recent studies revealed that infiltration and gradation have significant effects on the bearing capacity, water retention, and mechanical behaviors of unbound granular material [19].…”
Section: Introductionmentioning
confidence: 99%